Sustaining the properties of black soil in Central India through crop residue management in a conservation‐agriculture‐based soybean–wheat system. (4th May 2021) - Yadav, Devideen; Vishwakarma, Anand Kumar; Sharma, Narinder Kumar; Biswas, Ashis Kumar; Ojasvi, Prabhat Ranjan; Kumar, Dinesh; Kumawat, Anita; Singh, Deepak
Abstract: Soybean–wheat cropping system is the most commonly used in the black soil of India which produces enormous amounts of nutrient‐rich residues. However, black soil has some production limitations, such as rapid drying, high bulk density, low nutrients, and poor microbial populations, making it vulnerable to degradation. Optimal retention of soybean and wheat residues in black soil under the zero‐tillage (no‐till) system can improve soil properties and help protect the land from degradation. Thus, the main objective of this study was to test the effect of different levels of soybean and wheat residue retention on the physical, chemical, and biological properties of black soil. Therefore, an experiment was conducted in the zero‐tillagesoybean–wheat system at the Indian Institute of Soil Science, Bhopal, India from 2014 to 2018. In this study, the effect of four levels of soybean and wheat residue retention (no residue, 30, 60, and 90%) on soil properties was evaluated. Results revealed that soil organic carbon (C) significantly increased from 0.67 to 1.0% in 5 years through 90% residue retention. Retaining 90% (7.0 t) of soybean residue added 2.9 t C, 197.3 kg nitrogen (N), 32.4 kg phosphorus (P), and 89.7 kg potassium (K) in 5 years, while 6.2 t C, 85.7 kg N, 15.3 kg P, and 232.2 kg K were added through 90% (13.8 t) wheat residue during the same period. Different pools of soil C (oxidizable, labile, and particulate organic matter (OM)‐carbon), soil OM, soil moisture, soil porosity, available nutrients, and bacterial, fungal, and actinomycetes count was significantly enhanced due to retention of 90% residue over 60 and 30%. It was observed that retention of 90% soybean and wheat residues (7.0 and 13.8 t ha −1, respectively) significantly improved the physical, chemical, and biological properties of black soil in 5 years, therefore protected the soil from degradation.